Inadequacy of agricultural best management practices under warmer climates - Mohamed Khalil Zammali; Ali Nazemi; Elmira Hassanzadeh; Karl-Erich Lindenschmidt (Environmental Research Letters)
Agricultural best management practices (BMPs) are often implemented to reduce nutrient transport from farmland to downstream waterbodies. However, under the scenario of a changing climate, nutrient transport processes may be altered and BMPs may not be as effective. Using an ensemble of downscaled climate projections under moderate and high radiative forcings, we perform a hybrid climate assessment of BMPs in a large, flat, and primarily agricultural watershed in the Canadian Prairies. We quantify the total nitrogen delivery under current and future climate scenarios, with and without BMPs. Our findings reveal that BMP combinations, which are currently sufficient under historical climate conditions, may become inadequate to handle increased nitrogen under future climate conditions. We examine the enhancement of BMPs, conditioned to mean ensemble projections. Although updated combinations of BMPs show improvements in both the magnitude and cost of nitrogen removal compared to historical practices, their efficiency systematically declines as temperature rises. The decline rate of BMP efficiency is significantly larger under the high radiative forcing. Even by implementing all considered BMPs, we show that, at least under some realizations of future climate, the historical status-quo nitrogen state, in which no BMP is implemented, cannot be maintained. Our study demonstrates the reduced effectiveness of BMPs as the climate warms. To combat this, we recommend the immediate implementation of updated BMPs to slow down the build up of nitrogen. However, in innovations in physical, chemical, and biological remediation technologies would be needed in long term to control nitrogen loads coming from farmlands.